Effect of root pruning and trunk girdling on morphological, yield and fruit quality attributes in ‘YaLi’ pear (Pyrus spp.) trainedon the Cordon system - SHARMA, ANTIMA; SINGH, NAV PREM; GILL, PARMPAL SINGH; GILL, MANDEEP SINGH (The Indian Journal of Agricultural Sciences, 2026)
The study was carried out in 2022 and 2023 at Punjab Agricultural University, Ludhiana, Punjab to assess the effect of root pruning (RP), trunk girdling (TG) and RP + TG treatments in ‘YaLi’ pear (Pyrus spp. L.) cultivar trained on Cordon system for vegetative growth, fruit yield and quality attributes. The pooled data revealed significant reduction in annual shoot length, shoot diameter, internodal length, leaf area index, number of water sprouts/plant and pruned wood weight in the plants subjected to trunk girdling, root pruning and RP + TG treatments than the control (untreated plants). Leaf relative water content, total chlorophyll (SPAD) and macro nutrients content were reduced in all treatments except the control. The C:N ratio was substantially enhanced with TG and RP + TG compared to RP and the control. The reduction in net photosynthesis, stomatal conductance, intercellular CO2 concentration, rate of transpiration and higher plant photosynthetically active radiation (PAR), fruit yield efficiency and antioxidant activities were observed in the plants with girdling and root pruning treatments over the control. It was intended that the combination of root pruning + trunk girdling techniques is potential, valuable, low cost and eco-friendly to control tree growth and substantially improve return bloom, fruit yield and quality attributes of pear orchards under high density plantation.